The bacterial microbiome modulates the initiation of brain metastasis by impacting the gut-to-brain axis - Matteo Massara; Michelle Ballabio; Bastien Dolfi; Golnaz Morad; Vladimir Wischnewski; Eleni Lamprou; Joao Lourenco; Stéphanie Claudinot; Hector Gallart-Ayala; Rui Santalla Méndez; Annamaria Kauzlaric; Nadine Fournier; et al. (iScience)
Summary: Brain metastases (BrMs) are the most common brain tumors in patients and are associated with poor prognosis. Investigating the systemic and environmental factors regulating BrM biology represents an important strategy to develop effective treatments. Toward this goal, we explored the contribution of the gut microbiome to BrM development by using in vivo breast-BrM models under germ-free conditions or antibiotic treatment. This revealed a detrimental role of gut microbiota in fostering BrM initiation. We thus evaluated the impact of antibiotics and BrM outgrowth on the gut-brain axis. We found the bacterial genus Alistipes was differentially present under antibiotic treatment and BrM progression. In parallel, we quantified circulating metabolites, revealing kynurenic acid as a differentially abundant molecule that impaired the interaction between cancer cells and the brain vasculature in ex vivo functional assays. Together, these results illuminate the potential role of gut microbiota in modulating breast-BrM via the gut-to-brain axis.